Coinage Metal Compounds With 4-Methoxy-Diphenylphosphane Benzoate Ligand Inhibit Female Cancer Cell Growth - Luciani, Lorenzo; Galassi, Rossana; Wang, Junbiao; Marchini, Cristina; Cogo, Alessia; Di Paolo, Maria Luisa; Dalla Via, Lisa (Frontiers in Chemistry, 2022)
Abstract In the continuous effort to find new metal-based compounds as alternatives to platinum-related anticancer drugs, 11th group metal phosphane compounds have been thoroughly taken into consideration. Tris-arylphosphane metal derivatives have been extensively considered as heteroleptic metal compounds exhibiting remarkable cytotoxic activities. Functional groups in the aryl moieties modulate the activity reinforcing or eliminating it. Previous works have highlighted that the presence of hydrophilic groups in the phosphane ligands, such as COOH or OH, hampers the anticancer activity of gold azolate/PPh3 compounds. To increase the polarity of the triarylphosphane ligand without affecting the activity, we considered the preparation of esters starting from the 4-diphenylphosphane-benzoic acid. The resulting phosphanes are poorer donators than the PPh3, leading to poly-phosphane M(I) compounds, and they exhibit intense emissive properties. A homologous series of L3MX type compounds (where M = Au and X = Cl, M= Cu and X = BF4 and M = Ag and X = PF6) were obtained with the 4-methoxy-diphenylphosphane benzoate. The homologous metal compounds have been characterized by analytical and spectroscopic methods and, remarkably, their formation was associated with high frequencies of 31P NMR chemical shift variations (5-35 ppm in CDCl3). The new complexes and the ligand were evaluated on sensitive and cisplatin resistant human tumor cell lines. The ligand is ineffective on cells while the complexes exert a notable antiproliferative effect. The homologous series of the L3MX complexes were able to significantly reduce the cell viability of human triple-negative breast cancer cells (MDA-MB-231), representing the most aggressive subtype of breast cancer, and of ovarian carcinoma (A2780). Among these coinage metal compounds, L3AgPF6 results the most interesting, showing the lowest GI50 values in all cell lines. Interestingly, this silver complex is more cytotoxic than cisplatin, taken as reference drug. The investigation of the mechanism of action of L3AgPF6 in A2780 cells highlighted the induction of the apoptotic pathway, the depolarization of the mitochondrial inner membrane, and a significant accumulation in cells.